Oxidative injury in V79 Chinese hamster cells: protective - Fernandes, Ana S. (2013)
Oxidative cell injury could be induced by different reactive oxygen species (ROS) operating in multiple pathways. The present work is focused on three different models of oxidative stress: the xanthine/xanthine oxidase system (XXO), an extracellular superoxide anion generator; tert-butylhydroperoxide (TBHP), an analogue of lipid hydroperoxides; and doxorubicin (Dox), an anticancer drug. Superoxide and peroxyl radicals, among other ROS, could be effectively scavenged by MnTM-4-PyP, a polyfunctional catalytic antioxidant. In this report, we have addressed the role of MnTM-4-PyP on the protection against the cytotoxicity induced by the three aforementioned oxidants. The effect of MnTM-4-PyP (0.1–100 μM) was evaluated in V79 fibroblasts using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide reduction and the crystal violet assays, as well as the mitotic index. Also, the generation of intracellular ROS was studied by the fluorescent probe dihydroethidium. MnTM-4-PyP has shown significant protective effects against the cytotoxicity of XXO and TBHP, increasing the cell viability in approximately 40% and reducing the intracellular level of ROS. However, no considerable protection occurred against Dox. The three oxidants caused a mitotic index reduction that was not altered by MnTM-4-PyP. In summary, MnTM-4-PyP appears to be a promising agent for the protection against oxidative injury. However, it has shown differential responses, reinforcing the need to study different experimental models for the adequate evaluation of its potentialities as a catalytic antioxidant.